Novel 9-Steps Automatic AC Voltage Regulator based on Two Step-down Transformers - Hussain Attia (Institute of Advanced Engineering and Science, 2017)
A novel design and simulation results of 9-steps automatic AC voltage regulator based on one step-down transformer is presented in this paper. Avoiding the problem of surge at the AC load during controlling jump steps is done through the proposed design. Accurate and smooth controlling function is achieved as well. Instead of the necessity of increasing the number of taps of the used multi tap transformer for wide controlling range of fluctuated AC supply voltage, the proposed designed adopts using only two step down transformers with 10 Vrms, and 30 Vrms secondary voltages respectively. Through the controlling of the proposed design of AV voltage regulator, the resultant load voltage is equal the AC supply voltage as well as the suitable voltage step which may one of the following voltages; +40V, +30V, +20V, +10V, 0V, -10V, -20V, -30V, -40V. The electronic design is done Multisim software while the electrical circuit connection of step down transformers and relays contacts that is made by using PSIM software for power circuit design.